2011
DOI: 10.1080/03091929.2010.521748
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stratification and compressibility on anelastic convection in a rotating plane layer

Abstract: We study the effect of stratification and compressibility on the threshold of convection and the heat transfer by developed convection in the nonlinear regime in the presence of strong background rotation. We consider fluids both with constant thermal conductivity and constant thermal diffusivity. The fluid is confined between two horizontal planes with both boundaries being impermeable and stress-free. An asymptotic analysis is performed in the limits of weak compressibility of the medium and rapid rotation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
(27 reference statements)
3
11
0
Order By: Relevance
“…We have also made a comparison of the full anelastic equations with the entropy diffusion anelastic model that has been employed frequently (e.g., Jones et al 2009, Mizerski andTobias 2011). The linear stability analysis showed that the anelastic equations and entropy diffusion model possess qualitatively similar stability behavior as a function of stratification, though the two models give quantitatively different results.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…We have also made a comparison of the full anelastic equations with the entropy diffusion anelastic model that has been employed frequently (e.g., Jones et al 2009, Mizerski andTobias 2011). The linear stability analysis showed that the anelastic equations and entropy diffusion model possess qualitatively similar stability behavior as a function of stratification, though the two models give quantitatively different results.…”
Section: Discussionmentioning
confidence: 96%
“…To provide a close connection with previous work that has utilized the entropy diffusion model (e.g., Jones et al 2009, Mizerski andTobias 2011), the above equations are supplemented with isentropic boundary conditions given by…”
Section: Entropy Diffusion Modelmentioning
confidence: 95%
See 2 more Smart Citations
“…Typically, in Boussinesq formulations the vertical axis increases upwards, whereas in compressible studies it is taken downwards. In order to ease the comparison with Boussinesq models, we take the vertical axis to increase upwards in line with Mizerski and Tobias 32 . The existing studies of anelastic convection, linear and nonlinear, each consider a different formalism (discussed below) and therefore care has to be taken when comparing across the different models.…”
Section: Introductionmentioning
confidence: 99%